Representasi Etika Jurnalistik Investigasi Dalam Film Shattered Glass Karya Billy Ray (Analisis Semiotika Roland Barthes) - Selvia Puspita Ningsih; Nurseri Hasnah Nasution; Jufrizal (CV. ITTC INDONESIA, 2023)
Good and correct reporting must be in harmony with journalism ethics by prioritizing social responsibility to serve the information needs of society. This research is entitled,